2019
DOI: 10.1111/hel.12670
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori heteroresistance to clarithromycin in adults—New data by in situ detection and improved concept

Abstract: BackgroundClarithromycin (Cla) heteroresistance of Helicobacter pylori (H pylori) infections is commonly assessed by comparing the resistance status of antrum and corpus biopsy samples and by demonstrating the discrepancy between them (interniche heteroresistance). However, fluorescence in situ hybridization (FISH) technique is capable of showing the synchronous presence of susceptible and resistant bacteria (intraniche heteroresistance), enabling the detection of heteroresistant H pylori populations within on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…In 22 samples, we detected H pylori both susceptible and resistant to clarithromycin and levofloxacin, respectively. Patients with such a heteroresistant status still may benefit from clarithromycin‐ and/or levofloxacin‐based eradication treatments when compared with patients carrying exclusively resistant bacteria 15‐17 . An impact on eradication success may also depend on the kind of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In 22 samples, we detected H pylori both susceptible and resistant to clarithromycin and levofloxacin, respectively. Patients with such a heteroresistant status still may benefit from clarithromycin‐ and/or levofloxacin‐based eradication treatments when compared with patients carrying exclusively resistant bacteria 15‐17 . An impact on eradication success may also depend on the kind of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited number of cases and the retrospective nature of the study, our results should be considered somewhat preliminary and will require further confirmation. Based on our previous publications, it is clear that heteroresistant H. pylori infections account for about half of all clarithromycin-resistant cases (18,38). Therefore, further prospective studies with increased patient case number would be necessary to establish a more definite relationship between eradication success and bacterial load, as well as, to find further predictive factors to facilitate therapeutic decisions, and in result contribute to establishing a standard protocol for Cla-heteroresistant infections.…”
Section: Discussionmentioning
confidence: 99%
“…Cla-heteroresistance is frequent, but the currently used routine diagnostic susceptibility test methods (E-test, PCR, or the combination) are set to diagnose interniche heteroresistance only, which may undermine the actual heteroresistance rates (17,18,20,(26)(27)(28)(29)(30). In a previous study of our group, by applying FISH technique to gastric biopsy specimens, we demonstrated that the heteroresistance occurs in more than half (52%) of the Cla-resistant H. pylori infections (18). The most common form was found to be the intraniche heteroresistance occurring simultaneously in the antrum and the corpus of the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations